The Utility of Advanced Cardiovascular Imaging in Cancer Patients—When, Why, How, and the Latest Developments - Yu, Christopher; Pathan, Faraz; Tan, Timothy C.; Negishi, Kazuaki (Frontiers in Cardiovascular Medicine, 2021)
Cardio-oncology encompasses the risk stratification, prognostication, identification and management of cancer therapeutics related cardiac dysfunction (CTRCD). Cardiovascular imaging (CVI) plays a significant role in each of these scenarios and has broadened from predominantly quantifying left ventricular function (specifically ejection fraction) to the identification of earlier bio-signatures of CTRCD. Recent data also demonstrate the impact of chemotherapy on the right ventricle, left atrium and pericardium and highlight a possible role for CVI in the identification of CTRCD through tissue characterization and assessment of these cardiac chambers. This review aims to provide a contemporary perspective on the role of multi-modal advanced cardiac imaging in cardio-oncology.